Answer:
Step-by-step explanation:
In the attached figure, we have defined LM to be length x. Then the other lengths on side AC are ...
AM = LR = x/√3
RC = (2/√3)RK = (2/√3)(2/√3)x = 4/3x
Then the sum of lengths along AC is ...
AC = AM +ML +LR +RC
1 = x(1/√3 +1 +1/√3 +4/3) = x(7/3 +2/√3) = x(7√3 +6)/(3√3)
Then the value of x is ...
[tex]x=\dfrac{3\sqrt{3}}{7\sqrt{3}+6}=\dfrac{3\sqrt{3}(7\sqrt{3}-6)}{(7\sqrt{3})^2-6^2}=\dfrac{3(21-6\sqrt{3})}{3(49-12)}\\\\\boxed{MN=\dfrac{21-6\sqrt{3}}{37}}\\\\RK=\dfrac{2\sqrt{3}}{3}MN\\\\\boxed{RK=\dfrac{14\sqrt{3}-12}{37}}[/tex]